Blessing food as an effort to meet people's food needs during the Covid-19 pandemic - Purnanto, Arif Wiyat; Karimatunnisa, Afifah; Dewi, Mia Martina; Andaeni, Rizka Veny; Saputra, Setiyawan Adhi; Eman, Eman (Community Empowerment, 2021)
The Covid-19 pandemic has affected all aspects of people's life activities, including many people who have lost their jobs. This food donation program aims to help the community's food needs in the midst of the Covid-19 pandemic. There needs to be an attitude of sharing in reducing the burden of the impact of the current pandemic. Therefore, this program is one solution to help the community meet their food needs and can reduce the burden of the Covid-19 pandemic. This activity was carried out in 4 locations in the Magelang City, Magelang Regency, Temanggung Regency, and Wonosobo Regency. The distribution of food donations was enthusiastically welcomed by the residents. So that the poor can meet their food needs during the Covid-19 pandemic.